Intensity of fertilizer use in Latin America and the Caribbean (2006-2012) (2017)
One of the challenges of the sustainable development concept is the management and conservation of renewable natural resources, including soils and water. Hence, the use of fertilizers is important, since they can alter the edaphic ecosystems. The aim of this research was to determine in a comparative way the fertilizers intensity use in Latin American and the Caribbean countries from 2006 to 2012. The main source of consultation was the statistical yearbook of the United Nations Economic Commission for Latin America and the Caribbean (ECLAC). The methodological strategy consisted of five phases: 1) Static-comparative characterization, 2) Cluster analysis, 3) Z analysis, 4) Comparisons of ranges obtained by the countries according to the groups they belong, and building of a dendrogram, and 5) Multiple regression models. The results indicate that the countries with smallest surfaces are those where the use fertilizers is most intensive. This trait is particularly evident in the Caribbean. One of the explanatory factors in this regard the relatively less use of fertilizers by area in the larger nations, would be the establishment and prevalence of the agricultural model of “Latin American hacienda” system. In this type of productive structure, incomes are achieved through large extensions of the farm, rather than depending on a tech use, including the use of fertilizers. © 2017, Universidad Centroccidental Lisandro Alvarado (UCLA). All rights reserved.